Institutional Evolution and the Collaborative Development of Technology Transfer Capabilities. (November 2022) - Donegan, Mary; Feldman, Maryann
This article examines the development of university technology transfer operations at the Research Triangle region's three universities. Organized to commercialize university-based scientific inventions, this expertise was essential to university engagement in the region's long-term development. Early collaborative efforts to jump-start technology transfer in the region were promoted via a joint licensing consortium. Those early efforts—and their eventual devolution to the universities—are critical to understanding the region's subsequent development. We document a process of competing institutional logics and institutional interpretation, with officials from each campus continually interpreting the collaborative's value against their own institution's evolving needs.